Strengthening Literacy and Numeracy Competencies Based on Local Wisdom for Teachers to Design Contextual Learning - Akhmad Humaidi; Rahidatul Laila Agustina; Dina Huriaty (Universitas Lambung Mangkurat, 2024)
Barito Kuala Regency, especially Jejangkit District, lags behind other regions in South Kalimantan regarding human resources. According to the BPS of South Kalimantan Province, the Human Development Index for Barito Kuala Regency is in 13th position out of 14 districts from 2020 to 2022. Education is a strategic aspect of overcoming this problem. Teachers need to receive training on literacy and numeracy learning strategies to improve the quality of human resources, especially students in the younger generation. This community service activity aims to strengthen the literacy and numeracy competencies of elementary school teachers who are members of the Jejangkit District KKG by integrating learning with local wisdom. Local wisdom is contextual so students can more easily understand learning that is close to everyday life. This service activity uses the Participatory Action Research (PAR) method, which consists of five stages, namely to know, to understand, to plan, and to act in the form of On Service Training and On Job Training, as well as to change in the form of In-Service Training activities. This activity involved one trainer and 15 teachers representing 12 elementary schools in the Jejangkit District KKG. A total of 3 teachers from 3 schools also received intensive assistance in practising the material as examples for other participants. The evaluation instrument for this service program uses a questionnaire. Based on the data collected, this activity was successful in providing improvements in literacy and numeracy learning. The average post-test score (81.71) was higher than the pre-test (69.73). The teachers succeeded in designing learning that made students more focused on learning. This activity implies that teachers have succeeded in improving the competence and quality of learning in the classroom, especially literacy and numeracy for their students.